A two-layer frequency control method for large-scale distributed energy storage clusters. (December 2022) - Lin, Yujun; Li, Xing; Zhai, Baoyu; Yang, Qiufan; Zhou, Jianyu; Chen, Xia; Wen, Jinyu
Highlights: Distributed ESs are aggregated into clusters to reduce the computational burden. The frequency regulation and SoC balance of ESs are combined. Both the frequency deviation and rate of change of frequency are considered. The circulating currents are prevented to reduce the transmission losses. A detailed small-signal model is established to analyze the system stability. Abstract: A large number of small-capacity distributed energy storages (ESs) are expected to play an important role in grid frequency regulation. However, without suitable control scheme, it may lead to heavy computational burden and low utilizing efficiency. In this paper, a two-layer frequency control framework is proposed for large-scale distributed ESs that can be separated into several ES clusters. On the upper layer, the frequency regulation is achieved through distributed model predictive control (DMPC) among different ES clusters. The parallel computing of the distributed controllers reduces the optimization problem dimension brought by a large number of ES clusters. In addition, both the frequency deviation and rate of change of frequency are considered to achieve better frequency regulation. On the lower layer, state-of-charge (SoC) balance is considered within each cluster by the leader–follower consensus algorithm in a distributed mode, and it only requires communication between neighboring ESs in a cluster to aggregate for the upper layer. Unlike the conventional SoC balancing strategy, circulating currents are prevented to reduce the transmission losses. Moreover, a detailed small-signal model is established to show the impact of the proposed control strategy on the system stability. The effectiveness of the entire control scheme and the small-signal analysis are validated under a variety of scenarios by simulations. © 2017 Elsevier Inc. All rights reserved.